Internet security a jumpstart for systems administrators and IT managers - Speed, Tim.; Ellis, Juanita (Amsterdam ; London : Digital Press, 2003)
Internet Security incorporates not only the technology needed to support a solid security strategy but also those policies and processes that must be incorporated in order for that strategy to work. New methods of breaking into corporate networks are resulting in major losses. This book provides the latest information on how to guard against attacks and informs the IT manager of the products that can detect and prevent break-ins. Crucial concepts such as authentication and encryption are explained, enabling the reader to understand when and where these technologies will be useful. Due to the authors' experiences in helping corporations develop secure networks, they are able to include the newest methods for protecting corporate data. Shield data from both the internal and external intruder Discover products that can detect and prevent these break-ins Protect against major losses with the latest incident handling procedures for detecting and recovering data from new viruses Get details of a full security business review from performing the security risk analysis to justifying security expenditures based on your company's business needs.
The Internet and security -- The security review process -- Cryptography -- Secure networks -- Protecting your intranet from the extranet and Internet -- Authentication and authorization -- E-commerce : public key infrastructure -- Messaging security -- What are we doing here? -- Disaster recovery.
Includes index.
Includes bibliographical references (p. 321-389) and index.
Keywords: Internet -- Security measures; Computer networks -- Security measures; Computer security; Electronic books